Determinants for Foreign Direct Investment in the Baltic Sea Region - Nuutti Nikula; Markku Kotilainen (The Research Institute of the Finnish Economy (ETLA), 2013)
We have defined the Baltic Sea Region as consisting of the following countries: Denmark, Estonia, Finland, Germany, Latvia, Lithuania, Poland, Sweden, and Russia. We investigate foreign direct investment (FDI) flows from 1995 to 2010 to these countries econometrically. We use two basic models: the first one treats aggregate FDI inflows by countries, and the second focuses on bilateral FDI flows between country pairs. Because of limitations in data availability, the second model is built for a smaller group of countries. In this model we take into account the origin country of the FDI. Our results show that macroeconomic factors such as corporate taxes are important determinants for FDI flows. We notice that these factors and their effects vary between the Baltic Sea Region countries. Foreign trade with the investing country is also a statistically significant determinant for FDI, i.e. the countries that have trade with each other also invest in each other. On the other hand distance between countries doesn't explain FDI flows. Institutional factors such as EU membership or a common currency are not statistically significant in our estimations but this could be because of data limitations and because of the fact that these changes in countries' international status are incorporated in the other variables and are also foreseen by the investors.
Keywords: F21; F23; F13; F15; 330; Foreign direct investment (FDI); Baltic Sea Region; Denmark; Estonia; Finland; Germany; Latvia; Lithuania; Poland; Sweden; Russia; Auslandsinvestition; Gravitationsmodell; Ostseeraum